The association between isometric strength and cognitive function in adults with cerebral palsy - Heyn, Patricia C.; Tagawa, Alex; Pan, Zhaoxing; Reistetter, Timothy; Ng, Ted Kheng Siang; Lewis, Meredith; Carollo, James J. (Frontiers in Medicine, 2023)
Background: The literature supports quantifying the maximum force/tension generated by one's forearm muscles such as the hand grip strength (HGS) to screen for physical and cognitive frailty in older adults. Thus, we postulate that individuals with cerebral palsy (CP), who are at higher risk for premature aging, could benefit from tools that objectively measure muscle strength as a functional biomarker to detect frailty and cognitive decline. This study assesses the clinical relevancy of the former and quantifies isometric muscle strength to determine its association with cognitive function in adults with CP. Methods: Ambulatory adults with CP were identified from a patient registry and were enrolled in this study. Peak Rate of Force Development (RFD) and maximum voluntary isometric contraction of the quadriceps were measured using a commercial isokinetic machine, while HGS was collected with a clinical dynamometer. The dominant and non-dominant sides were identified. Standardized cognitive assessments, including the Wechsler Memory and Adult Intelligence Scales IV, Short Test of Mental Status, and the Patient-Reported Outcomes Measurement Information System (PROMIS®) were used to evaluate cognitive function. Results: A total of 57 participants (32 females; mean age 24.3 [SD 5.3]; GMFCS levels I–IV) were included in the analysis. Although dominant and non-dominant RFD and HGS measures were associated with cognitive function, non-dominant peak RFD showed the strongest associations with cognitive function. Conclusion: RFD capacity may reflect age-related neural and physical health and could be a better health indicator than HGS in the CP population.